Pemetaan Potensi Wisata Kuliner Di Desa Wisata Sayan Ubud - Putra, I Komang Cahyendra; Utama, I Putu; Sihombing, Irene Hanna H. (JURNAL GASTRONOMI INDONESIA, 2025)
This research aims to map and present the variety of culinary tourism potential in Sayan Tourism Village, Ubud District, Bali Province. Data collection techniques in this research include observation, interviews and documentation. Then analyzed using a descriptive qualitative approach. Based on the research results, this mapping includes several important aspects, namely: Hamlet Names, Halal and Non-Halal Food Categories, Types of Food, Place Names, and Main Menu. Based on the research results, researchers identified 18 halal food menus and 5 non-halal food menus. Apart from that, this research also found that there are 7 types of food in Sayan Tourism Village, consisting of Traditional Balinese, Vegan, Fusion, Asian, Western, Japanese, and Asian Western Fusion. This research provides a comprehensive picture of the culinary variety available in Sayan Tourism Village, which includes not only traditional Balinese food but also various types of international food. This shows the great potential of Sayan Tourism Village as a culinary tourism destination that can attract various tourist segments, both local and international.